A multi-perspective integrated framework of critical success factors for supporting on-line shopping - Varela, Maria Leonilde Rocha (2016)
E-commerce promotes economic growth by enabling online shops to compete within a global market scenario. There are critical success factors that permit to distinguish a good business on the Internet and this knowledge may allow reaching an important competitive advantage for business sustainability. As many disciplines are involved, when determining critical success factors, e-commerce requires an effective coordination and integration in a collaborative way. In e-commerce, as well as in any other ecosystem, the breaking down of some integrating elements may provoke a collapse on the whole system. The various stakeholders involved in a given business should, therefore, be involved and work together to achieve a high quality product that fully satisfies the end customer's needs and wishes. To meet the above requirement, this paper proposes a multi-perspective critical success factors (MPCSF) model for online shopping.